Innovation and values a european perspective - GALARRAGA EZPONDA, Auxkin (Revista Española de Investigaciones Sociológicas, 2024)
Innovation and values: a european perspective Javier Echeverría Ezponda Center for Basque Studies-University of Nevada, 2014